5.6k views
1 vote
Is -2(3x-7) equivalent to 19+12x-5-6x? YES or NO???

User Robin Sage
by
6.1k points

1 Answer

0 votes

Answer:





6. 6x-21=33+9x 7. -15x=-5(3x+7) 8. 16x-19=113-6x 9. -19x-34=56-x 10. -6(4x+3)=6(4x-3)?

6. 6x-21 = 33 +9x

+21 + 21

6x = 54 + 9x

-9x -9x

-3x = 54

/3 /3

x = -18

7. -15x = -5(3x+7)

First multiply the -5 to the other numbers.

-15x = -15x - 35

0x = -35

7 is impossible I believe.

8. 16x-19 = 113-6x

+6 +6

22x - 19 = 113

+ 19 +19

22x = 132

/22 /22

x = 6

9. -19x - 34 = 56 - x

+19x +19x

-34 = 56 + 18x

-56 -56

-90 = 18x

/18 /18

x = -5

10. -6(4x+3) = 6[4x-3]

-24x - 18 = 24x - 18

+18 +18

-24x= 24x

x = 0, since only zero can make the equation true.

User Sabahattin
by
5.5k points